2021
DOI: 10.3390/cancers13174483
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Therapeutic Potential of the OIP5 Network in Papillary Renal Cell Carcinoma

Abstract: Papillary renal cell carcinoma (pRCC) is an aggressive but minor type of RCC. The current understanding and management of pRCC remain poor. We report here OIP5 being a novel oncogenic factor and possessing robust prognostic values and therapeutic potential. OIP5 upregulation is observed in pRCC. The upregulation is associated with pRCC adverse features (T1P < T2P < CIMP, Stage1 + 2 < Stage 3 < Stage 4, and N0 < N1) and effectively stratifies the fatality risk. OIP5 promotes ACHN pRCC cell prolif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…It has been reported that OIP5 induces papillary renal carcinoma cell proliferation [ 26 ]. In glioblastoma, cells exhibit obvious reduction of division when OIP5 is knocked down, whereas its recovery enhances proliferation ability [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that OIP5 induces papillary renal carcinoma cell proliferation [ 26 ]. In glioblastoma, cells exhibit obvious reduction of division when OIP5 is knocked down, whereas its recovery enhances proliferation ability [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…KIF18B is also illustrated to be the oncogenesis to promote tumor progression and enhance therapeutic resistance (Li B. et al, 2020;Liu et al, 2020;Jiang J. et al, 2021). OIP5 upregulation is observed in human cancers (Chow et al, 2021), and seems to be linked to drug resistance (Rodrigues-Junior et al, 2018). NUF2 is found to be a prognostic biomarker and therapeutic target which is correlated with the immune infiltration in patients with cancer Shan et al, 2021;Xie et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Chow et al [6] have analyzed the role of OPA interacting protein 5 (OIP5) in 20 papillary renal cell carcinomas (PRCC) and 37 (CCRCC). OIP5 up-regulation has been associated with biological aggressiveness in a broad spectrum of malignant neoplasms, PRCC included.…”
Section: Renal Cancermentioning
confidence: 99%